An Interval Fuzzy-Valued M-TOPSIS Model for Design Concept Selection - Aikhuele, Daniel Osezua; Faiz, Mohd Turan (Universiti Malaysia Pahang, 2016)
This paper presents an easy and a reliable approach for evaluating and selecting product design concept, by using a modified improved score function and a weighted Normalized Hamming distance method for calculating the separation measures of alternatives in a fuzzy Delphi and Modified Technique for Order Preference by Similarity to the Ideal Solution model. The proposed model has successfully been implemented to select the most appropriate printed circuit board (PCB) design for an electronic related manufacturing company located around Pekan area in Malaysia and it has also been applied for a modified hypothetical example originally presented by Rouyendegh,[1], which is based on the selection of a preferred Car as a reference for a new design. The result from this study is hoped to serve as a guide for companies/managers planning to select new designs for their products as well as in the evaluation of their current practices.